Analisis Kebijakan Sekolah Terhadap Inovasi Pedagogik dan Dampaknya Terhadap Motivasi Belajar Peserta Didik di SMPS 2 Al-Muhajirin - Sri Rahmawati; Selasih Margi Susanti; Wilda Suryaningrat; Ricky Yoseptry (STKIP PGRI SITUBONDO, 2025)
The background of this study stems from the need for schools to address the challenges of modern education through the strengthening of policies that encourage teacher creativity, the use of technology, and the development of student-centered learning strategies. School policies that support pedagogical innovation are expected to enhance the achievement of optimal learning outcomes. This study employs a qualitative approach using a case study method. The results indicate that school policies at SMPS 2 Al-Muhajirin have been directed toward strengthening pedagogical innovation through teacher training programs, the utilization of digital technology, the cultivation of an active learning culture, and the improvement of learning facilities. The implementation of pedagogical innovation is reflected in the use of collaborative and project-based learning models, technology integration, and differentiated approaches tailored to students’ needs. These innovations have been shown to have a positive impact on students’ learning motivation, as evidenced by increased participation, interest, enthusiasm, and learner autonomy. However, the study also identifies several obstacles, including limited technological facilities, variations in teachers’ competencies in adapting innovations, and a lack of continuous mentoring. Overall, the study concludes that well-directed and consistent school policies play a crucial role in promoting pedagogical innovation, and that such innovation significantly contributes to enhancing students’ learning motivation. This study recommends strengthening continuous professional development, optimizing digital facilities, and enhancing collaboration among teachers to ensure the sustainability of pedagogical innovation at SMPS 2 Al-Muhajirin.